Navigation of polar orbiter images for solar radiation mapping - Sritharan, V.; Exell, Robert H.B.; Mora, Jean-Claude; Lukens, John E.; The Government of France (Bangkok : Asian Institute of Technology, 1990)
An operational software written in FORTRAN language for the navigation of NOAA-A VHRR images, to be used for solar radiation mapping, has been installed in the IBM main frame computer at AIT. The navigation software is based on an algorithm developed by NESDIS-NOAA and includes three software packages: GHA Table Generation, AELDS, and Brouwer-Lyddane. The GHA Table Generation package developed by NESDIS-NOAA is modified to be compatible with the IBM main frame computer system at AIT. The AELDS package for navigation developed by NESDIS-NOAA is modified to incorporate the Brouwer-Lyddane orbit generation package which was developed by Brouwer and modified by Lyddane. An A VHRR-HRPT image obtained from Malaysia is navigated and the results proved the satisfactory working of the navigation software. The report includes the explanation of the navigation theory and algorithm, the implementation of the navigation algorithm using the above mentioned software packages, and a manual for operating the navigation software. The manual also includes an example of navigation of an A VHRR-HRPT image. A method is also suggested for the processing of the A VHRR-APT images for solar radiation mapping.
A thesis submitted in partial fulfillment of the requirements of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Solar radiation -- Maps